IMPLEMENTING COVID-19 STANDARD OPERATION PROCEDURE (SOP) IN MALAYSIA CONSTRUCTION INDUSTRY: CHALLENGES AND STRATEGIES - Haryati Shafii,; Nur Afifah Mohd Radzi,; Azlina Md Yassin,; Haidaliza Masram, (International Journal of Property Sciences (E-ISSN: 2229-8568), 2022)
The COVID-19 disease has impacted the performance of all industries, including the construction industry. In order to curb the spread of the disease, the government has conducted Movement Control Order (MCO). Consequently, a construction project is not allowed to be operated unless the implementation of the new SOP aims to curb the spread of COVID-19 disease among workers on the construction site. The operation of the construction site has resulted in new clusters of COVID-19 in the early phase of the outbreak which led to the project shut down. The objective of this study is to identify the challenges of implementation of SOP during the outbreak of COVID-19 from the contractor’s perspective and to suggest a solution for controlling the effects of the COVID-19 outbreak at the construction site. In collecting data and responses from the respondents, interviews were held through the telephone conversation and video conferencing with nine (9) contractors in Cheras, Kuala Lumpur. The selection was made through the purposive sampling technique in which the contractors were selected from the contractor listing on the Malaysian Construction Industry Development Board (CIDB) website. Content analysis is used to identify the main challenges. Results from interviews found four (4) challenges faced by contractors and five (5) solutions for mitigating the effect of an outbreak. The challenges include wearing face masks, maintaining social distancing, securing authority approval letter, and restriction of workers’ numbers. On the other hand, the solutions that are highlighted include proper planning and scheduling, complying with COVID-19 standard operating procedures (SOP), controlling the movement of workers, providing all workers’ vaccination, and conducting regular COVID-19 tests. These findings have shown that having SOP for COVID-19 has posed challenges to the activities on the construction sites. As such, the findings intend to increase the awareness among construction companies on the challenges towards the implementation of the best practices to overcome these challenges.